2020
DOI: 10.1108/jocm-02-2020-0061
|View full text |Cite
|
Sign up to set email alerts
|

Ideological tensions amidst rapid and continuous organizational change in healthcare

Abstract: PurposeThe aim of this study was to explore the nature of frontline nurses' experiences of living with rapid and continuous organizational change.Design/methodology/approachA critical hermeneutic approach was utilized. This was a qualitative inquiry theoretically guided by critical management studies.FindingsParticipants recognized that many change initiatives reflected an ideological shift in healthcare that supported a culture of service, whilst sacrificing a culture of care. A culture of service prioritized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(50 citation statements)
references
References 48 publications
1
49
0
Order By: Relevance
“…Although many authors reported homogeneity among their definitions of change fatigue, some had divergent definitions. For example, some authors recognized change fatigue manifests as a resistance to change or cynicism about change (Davis, 2002; Authors suggested that rapid and continuous practice initiatives have become the norm due to the constant need to improve healthcare delivery (Brown et al, 2018;Davis, 2002;McMillan, 2018;McMillan & Perron, 2013;Muir et al, 2021;Vestal, 2013). The current healthcare landscape of continued improvement results in Brown, 2016;Brown et al, 2018;Brown & Abuatiq, 2020;Summer Bryant, 2020;Camilleri et al, 2019;Gee et al, 2017;Kapping, 2021;Lind et al, 2018;Mayer & Hammelef, 2013;McMillan, 2018;McMillan & Perron, 2013, 2020bMuir & Keim-Malpas, 2020;Muir et al, 2021;Reineck, 2007;Szumilas, 2015;Valusek, 2007. Divergent definitions of change fatigue Davis, 2002;Huynh et al, 2018;Kapping, 2021;Mayer & Hammelef, 2013;Metusela et al, 2021;Reineck, 2007;Vestal, 2013. No definition provided Davis, 2002;Ead, 2015;Gee et al, 2017;Muir & Keim-Malpas, 2020;Wozniak et al, 2020.…”
Section: Divergent Definitions Of Change Fatiguementioning
confidence: 99%
See 3 more Smart Citations
“…Although many authors reported homogeneity among their definitions of change fatigue, some had divergent definitions. For example, some authors recognized change fatigue manifests as a resistance to change or cynicism about change (Davis, 2002; Authors suggested that rapid and continuous practice initiatives have become the norm due to the constant need to improve healthcare delivery (Brown et al, 2018;Davis, 2002;McMillan, 2018;McMillan & Perron, 2013;Muir et al, 2021;Vestal, 2013). The current healthcare landscape of continued improvement results in Brown, 2016;Brown et al, 2018;Brown & Abuatiq, 2020;Summer Bryant, 2020;Camilleri et al, 2019;Gee et al, 2017;Kapping, 2021;Lind et al, 2018;Mayer & Hammelef, 2013;McMillan, 2018;McMillan & Perron, 2013, 2020bMuir & Keim-Malpas, 2020;Muir et al, 2021;Reineck, 2007;Szumilas, 2015;Valusek, 2007. Divergent definitions of change fatigue Davis, 2002;Huynh et al, 2018;Kapping, 2021;Mayer & Hammelef, 2013;Metusela et al, 2021;Reineck, 2007;Vestal, 2013. No definition provided Davis, 2002;Ead, 2015;Gee et al, 2017;Muir & Keim-Malpas, 2020;Wozniak et al, 2020.…”
Section: Divergent Definitions Of Change Fatiguementioning
confidence: 99%
“…Rapid and continuous change Brown et al, 2018;Camilleri et al, 2019;Davis, 2002;Ead, 2015;Havaei et al, 2021;Lind et al, 2018;McMillan, 2018;McMillan & Perron, 2013, 2020bMuir et al, 2021;Szumilas, 2015;Tracy, 2006;Vestal, 2013.…”
Section: Factors Preceding Change Fatiguementioning
confidence: 99%
See 2 more Smart Citations
“…Dysfunction of health systems related to the epidemic situation affects human health and life (Wong et al, 2020). In such conditions, the healthcare system requires transformation, reform and continuous improvement (McShane et al, 2020;McMillan and Perron, 2020). A substantive discussion on changes in the organisation and management of medical entities and their impact on the health and safety of the patient become necessary.…”
Section: Health and Health Protectionmentioning
confidence: 99%